2023
DOI: 10.3390/antiox12030716
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Nutritional Composition and Bioactive Compounds in Different Cocoa Powders

Abstract: Cocoa, the main derivative of the seeds of Theobroma cacao L., has been recognized to have several effects on human health including antioxidant and neuro- and cardio-protective effects, among others. These effects have been attributed mainly to its bioactive compounds. In this context, the aim of this work is to evaluate the nutritional composition, bioactive compounds (i.e., phenolic compounds, procyanidins and methylxanthines) and the antioxidant activity of seven different cocoas (alkalized and non-alkaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…Numerous antioxidants, such as caffeine, theobromine, and theophylline, as well as soluble phenolic compounds (phenolic acids, catechin, epicatechin, and proanthocyanidins) and insoluble polymeric phenolics (catechin, epicatechin, and theophylline) are found in cocoa [ 32 ]. Using the Folin-Ciocalteu method, Razola-Diaz et al [ 33 ] measured the GAE/g total polyphenol contents of various cocoa powders from different growing regions. These results ranged between 9.2 and 57.4 mg.…”
Section: Resultsmentioning
confidence: 99%
“…Numerous antioxidants, such as caffeine, theobromine, and theophylline, as well as soluble phenolic compounds (phenolic acids, catechin, epicatechin, and proanthocyanidins) and insoluble polymeric phenolics (catechin, epicatechin, and theophylline) are found in cocoa [ 32 ]. Using the Folin-Ciocalteu method, Razola-Diaz et al [ 33 ] measured the GAE/g total polyphenol contents of various cocoa powders from different growing regions. These results ranged between 9.2 and 57.4 mg.…”
Section: Resultsmentioning
confidence: 99%
“…Felice et al [ 45 ] reported 7105 mg GAE/100 g FW in cocoa husk extracts. Razola-Diaz et al [ 46 ] indicated the TPC of cocoa from different countries. For example, cocoa beans from Peru had a TPC of 57.40 mg GAE/g DW; cocoa beans from Venezuela showed a TPC of 34.4 mg GAE/g DW while West African cocoa beans had a TPC of 9.2 mg GAE/g DW.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, the technological process related to the processing of cocoa beans for the manufacture of cocoa products affects the flavanol profile [9] in a qualitative and quantitative way. For instance, high temperatures and roasting times lead to the loss of bioactive compounds of interest, such as flavanols [71,72].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cocoa contains flavonoids such as epicatechin, quercetin and isoquercetin; flavones such as luteolin and apigenin; flavanones such as naringenin; anthocyanins and phenolic acids (Figure 1). These compounds are highly related to antioxidant activity [9]. Specifically, cocoa flavanols benefit the cardiovascular system, have antiinflammatory properties, reduce insulin resistance and enhance the growth of beneficial gut microbiota [1,3,10,11].…”
Section: Introductionmentioning
confidence: 99%